2021
DOI: 10.1016/j.mtbio.2021.100175
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of fluorescent single-walled carbon nanotubes within C. elegans nematodes in the near-infrared window

Abstract: Caenorhabditis elegans ( C. elegans) nematodes serve as a model organism for eukaryotes, especially due to their genetic similarity. Although they have many advantages like their small size and transparency, their autofluorescence in the entire visible wavelength range poses a challenge for imaging and tracking fluorescent proteins or dyes using standard fluorescence microscopy. Herein, near-infrared (NIR) fluorescent single-walled carbon nanotubes (SWCNTs) are utilized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 97 publications
(125 reference statements)
0
26
0
Order By: Relevance
“…The suspension was centrifuged twice at 16100 rcf for 90 min, where after each centrifugation step, 80% of the supernatant was collected and the rest was discarded. The resulting DNA-SWCNT concentration was measured by absorbance spectroscopy (Shimadzu UV-3600 Plus) , using an extinction coefficient of ε 632 nm = 0.036 L mg –1 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…The suspension was centrifuged twice at 16100 rcf for 90 min, where after each centrifugation step, 80% of the supernatant was collected and the rest was discarded. The resulting DNA-SWCNT concentration was measured by absorbance spectroscopy (Shimadzu UV-3600 Plus) , using an extinction coefficient of ε 632 nm = 0.036 L mg –1 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, SWCNTs emit bright fluorescence in the nIR range (900-1400 nm), which does not photobleach nor blink. [17] Moreover, given proper functionalization, they are highly biocompatible, [18,19] and were successfully utilized as imaging and sensing probes in various applications such as within plants, [14,20] live cells, [21,22] animals, [23][24][25] and brain tissue, [26,27] for example, the brain extracellular space (ECS). [28] For sensing, functionalized SWCNTs can bind specific analytes such as proteins, small molecules, metal ions, or bacteria, and exhibit fluorescence modulations upon interaction, whereas for imaging, they can be easily tracked in complex biological environment owing to their nIR fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…[28] For sensing, functionalized SWCNTs can bind specific analytes such as proteins, small molecules, metal ions, or bacteria, and exhibit fluorescence modulations upon interaction, whereas for imaging, they can be easily tracked in complex biological environment owing to their nIR fluorescence. [24,[29][30][31][32][33][34] In order to fully exploit SWCNTs as optical probes for both spatial and temporal information, the nanotubes should be individually imaged, tracked, and resolved. [35] One of the challenges is the heterogeneity of SWCNT samples, stemming from the synthesis and suspension procedures, which result in a wide distribution of SWCNT lengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NIR-fluorescence emission of SWCNTs depends on their close environment. , Changes in their close proximity, e.g., by analyte binding, are translated into changes in their fluorescence properties, i.e., emission wavelength shifts or fluorescence intensity changes. ,, Thus, SWCNTs can be utilized as NIR-fluorescence sensors that do not suffer from photobleaching or blinking, allowing for long-term measurements. , Successful integration of SWCNTs into hydrogels while taking advantage of their fluorescence properties as analyte-specific sensors has been shown. , Several studies also demonstrated the feasibility of SWCNTs integrated into hydrogels as implantable sensor platforms , for NIR-imaging and spectroscopy in tissue. , …”
mentioning
confidence: 99%